Implementasi Metode Multimedia Development Life Cycle (MDLC) Dalam Perancangan Aplikasi Augmented Reality Yang Memperkenalkan Budaya Suku Alas di Aceh - Rizki Aidil Akbar; Mufida Khairani (LKP Unity Academy, 2025)
The rapid development of information technology has significantly transformed the way information is delivered, including efforts to preserve local culture. This research focuses on the implementation of the Multimedia Development Life Cycle (MDLC) method in designing an Augmented Reality (AR) application aimed at introducing the cultural heritage of the Alas Tribe in Southeast Aceh. The Alas Tribe culture, which is rich in traditional values such as traditional houses, clothing, dances, and local wisdom, is increasingly threatened by modernization and the lack of interactive media that can attract the younger generation. Therefore, an innovative digital solution is needed to present cultural information in an interactive, engaging, and accessible way. The MDLC method was chosen because it provides a systematic framework consisting of concept, design, material collecting, assembly, testing, and distribution. Each stage was applied in a structured manner to ensure that the development process runs effectively and efficiently. The AR application enables users to interact with 3D objects representing elements of the Alas Tribe culture through Android devices, offering an immersive learning experience. User testing was conducted using questionnaires, and the results showed that most respondents found the application engaging, easy to understand, and useful for learning about local culture. The findings demonstrate that implementing the MDLC method successfully produces an effective AR application as a medium for cultural education and promotion. Beyond functioning as an educational tool, the application also contributes to cultural preservation and supports the development of the tourism sector in Southeast Aceh. For future development, it is recommended to expand the application by adding more cultural objects, integrating interactive quizzes, and enabling cross-platform compatibility to reach a wider audience. Keywords: Augmented Reality, Multimedia Development Life Cycle, MDLC, Alas Tribe Culture, Learning Media, Cultural Preservation.